Leakage Current Waveforms and Arcing Characteristics of Epoxy Resin for Outdoor Insulators under Clean and Salt Fogs - Suwarno Suwarno; S. K. Ardianto (Journal of Engineering and Technological Sciences, 2008)
Ceramic  outdoor  insulators  have  been  used  in  high  voltage transmission lines since long time ago. Due to superiority in their resistance to pollution, recently, polymeric outdoor insulators are widely used. Epoxy resin is one  polymer  which  shows  good  properties  for  outdoor  insulation.  During service,  outdoor  insulators  may severe a certain degree of pollution  which may reduce  their  surface  resistance.  Leakage  current  (LC)  usually   increase  and degradation  may  take  place.  This  paper  reports  experimental  results  on  the leakage current  waveforms and arcing characteristics of epoxy resin  under clean and salt fog. The samples used are blocks of epoxy resin with dimension of 250 x  50  x  20  mm3 .  The  samples  were  put  in  a  test  chamber  with  dimension  of 900x900x1200 mm3 with controllable humidity  and pollution conditions. Clean and  salt  fog  were  generated  according  to  IEC  60-1  and  507.  The  arcing experiment  was  done  with  incline  plane  test  in  accordance  with  IEC  587.  AC voltage  in the range from 5 kV to 50 kV with frequency of 50 Hz  was applied. The LC waveforms  up to flash over  were measured. The magnitudes as well as harmonic  content  of  the  LC  were  analyzed.   The  correlation  between  LC waveforms  and  dry  band  arching  phenomenon  was  elaborated.  Visual observation  of  the  arc  on  the  sample  surfaces  was  observed  using  a  video camera. Experimental results indicated that LC magnitude on clean  samples was slightly affected by humidity (RH). However, under salt fog, RH greatly affected the LC magnitude. The flashover voltage of clean samples under salt fog reduced significantly  for  fog  conductivity  of  more  than  1.2  mS/cm.  Kaolin-polluted samples under salt fog showed an Ohmic behaviour. The LC magnitude was high and a large discrepancy of LC magnitude was observed for high applied voltage of  larger  than  25  kV.  The  largest  LC  magnitude  was  observed  on  salt-kaolin polluted samples under clean fog at high RH. LC waveforms analysis indicated that in general LC waveforms were distorted from sinusoidal. For clean samples under clean fog, THD  of LC decreased with RH but slightly increased with the applied voltage. Large distortion at the peak of LC waveform  was observed on kaolin  polluted  sample  under  salt  fog  of  3.6  mS/cm  and  high  RH  and  high applied voltage. This correlates with corona arc on the sample surface. Similar behaviour  was  observed  on  kaolin-salt  polluted  samples  under  clean  fog. Tracking arc experiment indicated that arc length LC magnitude and arc intensity increased with the pollutant conductivity. The THD also significantly increased with  pollutant  conductivity.  At  conductivity  of  less  than  0.6  mS/cm  the unsymmetrical  LC  waveforms  were  obtained.  However,  symmetrical  LC waveforms were observed for conductivity of 0.9 and 1.2 mS/cm. The change of LC magnitude and waveform at different condition of samples may be useful for the diagnostics of insulator condition.